Chemodiversity and Antibacterial Activity of the Essential Oil of Leaves of Croton argyrophyllus. Issue 10 (29th September 2020) - de Araújo, Lidiane Gomes; Veras, Germano; de Oliveira Alves, João Victor; Oliveira de Veras, Bruno; da Silva, Márcia Vanusa; Bacalhau Rodrigues, José Filipe; Lia Fook, Marcus Vinicius; Sagoe Amoah, Solomon Kweku; da Conceição de Menezes Torres, Maria
Abstract: The Croton argyrophyllus leaf essential oil has anti‐inflammatory, antioxidant, cytotoxic among other activities. However, there are chemical composition variations in the literature. This work reports the first study of the intraspecific chemical variation of C. argyrophyllus population from Pernambuco state, Brazil. The essential oils of nine specimens (OCA1 to OCA9) were analyzed by GC/MS and NIR to identify the chemical compositions and to verify the similarities between the analyzed samples. These analyses resulted in the identification of bicyclogermacrene (mean 38.42 %), ( Z )‐caryophyllene (mean of 14.06 %), epi ‐longipinanol (mean of 9.78 %) and germacrene B (mean of 9.1 %) as the major constituents, as well as the same chemical markers for all oil samples. However, these are different to those that were previously registered in the literature for C. argyrophyllus essential oil. The data obtained from the analysis by NIR spectroscopy were treated by PCA and HCA and showed similarities in the chemical samples' profile. By statistical analyses three clusters were obtained: OCA1‐6, OCA7‐8 and OCA9. All these groups were potentially active against Staphylococcus aureus . However, the OCA7‐8 group was the most active. Abstract :